Tatalaksana Status Epileptikus Terkini pada Anak - Jose M. Mandei; Praevilia M. Salendu (Universitas Sam Ratulangi, 2023)
Absract: Status epilepticus is one of the most common pediatric neurologic emergencies in children with progressive benzodiazepine pharmaco-resistance due to neurotransmitter receptor disturbance. This has led to revisions of definitions and guidelines to emphasize early treatment and faster escalation. The initial management of the stabilization phase is followed by the administration of benzodiazepines as the first line. Second-line medications such as valproate, fosphenytoin, or levetiracetam, or phenobarbital are recommended, and at this point there is no clear evidence that one of these options is better than the other. If seizures persist after second-line drugs, refractory status epilepticus may be established. Treatment of refractory status epilepticus consists of bolus doses and continuous infusion titration with third-line drugs. In conclusion, potential therapeutic approaches for future study may require consideration of interventions that may speed the diagnosis and treatment of status epilepticus. Major advances in the clinical field with new definitions and classifications give the clinicians a better guidance on when to treat, how aggressively to treat, and how to avoid over- or under-treating the condition of status epilepticus. Keywords: status epilepticus; management; children Abstrak: Status epileptikus merupakan salah satu kedaruratan neurologis yang paling umum pada anak dengan farmakoresistensi benzodiazepine progresif karena gangguan reseptor neurotransmiter. Hal ini menyebabkan dilakukannya revisi definisi dan pedoman untuk menekankan pengobatan dini dan eskalasi yang lebih cepat. Tatalaksana awal fase stabilisasi dilanjutkan pemberian benzodiazepine sebagai lini pertama. Pengobatan lini kedua seperti valproate, fosphenytoin, atau levetiracetam, atau fenobarbital direkomendasikan, dan pada titik ini tidak ada bukti yang jelas bahwa salah satu dari opsi ini lebih baik daripada yang lain. Jika kejang berlanjut setelah obat lini kedua, status epileptikus refrakter dapat ditegakkan. Pengobatan status epileptikus refrakter terdiri dari dosis bolus dan titrasi infus kontinu dengan obat lini ketiga. Simpulan studi ini ialah pendekatan terapeutik potensial untuk studi masa depan mungkin memerlukan pertimbangan intervensi yang dapat mempercepat diagnosis dan pengobatan status epileptikus. Kemajuan besar dalam bidang klinis dengan definisi dan klasifikasi baru memberikan panduan yang lebih baik kepada dokter tentang kapan harus mengobati, seberapa agresif untuk mengobati, dan bagaimana menghindari pengobatan yang berlebihan atau kurang dari kondisi stastus epileptikus. Kata kunci: status epileptikus; tatalaksana; anak